Mapping Research Trends in the Development of Local Wisdom-Based Teaching Modules to Improve Science Literacy: A Review - Riska Dia Sapitri; Devi Ayu Septiani; Rizka Sofia Irawan; Ryya Aulia Assiri; Sri Suci Lestari (Current Educational Review, 2026)
Local wisdom-based learning modules are teaching materials that integrate cultural practices, values, and local environmental contexts to create meaningful science learning experiences. In the context of science learning, the use of local wisdom-based modules has been proven effective in improving students' scientific literacy, as students not only understand the concepts but also relate them to real phenomena in their daily lives. This study aims to identify and analyze research trends regarding the development of local wisdom-based learning modules to improve scientific literacy. The methods used are descriptive and analytical. Data were obtained from documents indexed by Google Scholar and Dimensions for the period 2016–2025 using the Publish or Perish and Dimension.ai tools. The data analyzed included the type of publication, publication source, and the most cited research title. Data analysis was conducted using bibliometric methods with the help of VOSviewer software. The results of the analysis show that the research trend from 2016 to 2025 experienced a significant increase, although there was a slight decrease in 2025 due to the incompleteness of the current year's data. Numerous documents, including articles, proceedings, book chapters, preprints, monographs, and edited books, discuss the development of local wisdom-based modules to strengthen scientific literacy. Keywords frequently used in this research include: local wisdom, science literacy, education, culture, digital literacy, and learning.